2008
DOI: 10.1007/s12124-008-9067-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Repetition in Bonobo–Human Conversation: Creating Cohesion in a Conversation Between Species

Abstract: Ape language research has primarily focused on specific isolated language features. In contrast, in research into human language, traditions such as conversational analysis and discourse analysis propose to study language as actual discourse. Consequently, repetitions are seen as accomplishing various discursive and pragmatic functions in human conversations, while in apes, repetitions are seen as rote imitations and as proof that apes do not exhibit language. Tools from discourse analysis are applied in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
(22 reference statements)
1
17
1
Order By: Relevance
“…If successful in obtaining the banana, subjects never continued to signal, but if unsuccessful they tended to elaborate their communicative efforts by switching to new signals, suggesting an apparent attempt to rectify an unsuccessful communication event and misunderstanding. With our third analysis, we showed that, similarly to human infants interacting with adults 7 52 and language-trained bonobos interacting with their caretakers 14 15 , subjects adapted their signal production according to whether or not they knew the recipient. In particular, they used more repetitions with a familiar recipient but elaborated more, by using new signals with an unfamiliar one.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…If successful in obtaining the banana, subjects never continued to signal, but if unsuccessful they tended to elaborate their communicative efforts by switching to new signals, suggesting an apparent attempt to rectify an unsuccessful communication event and misunderstanding. With our third analysis, we showed that, similarly to human infants interacting with adults 7 52 and language-trained bonobos interacting with their caretakers 14 15 , subjects adapted their signal production according to whether or not they knew the recipient. In particular, they used more repetitions with a familiar recipient but elaborated more, by using new signals with an unfamiliar one.…”
Section: Discussionmentioning
confidence: 89%
“…Results of these studies have regularly been interpreted in terms of language-relevant capacities (e.g. 11 12 13 ), including the claim that bonobos are capable of taking into account shared knowledge when interacting with familiar humans 14 15 . A general conclusion from this literature is that key cognitive abilities necessary for language were already present in the common ancestor of modern humans, chimpanzees and bonobos.…”
mentioning
confidence: 99%
“…For example, apes who know researchers with whom they work may be more likely to take and understand task directions, remain on task longer, and engage in unfamiliar (and, to apes, sometimes meaningless or irrelevant) tasks, than apes who are tested with relative strangers with whom they have no relationship. Finally, familiar researchers who have positive individualized relationships with their subjects, based on shared experience and knowledge, will likely be able to better interpret ape behavior [e.g., Matsuzawa, 2006;Pedersen & Fields, 2009].…”
Section: Ape (Animal) Research Beyond the Zoomentioning
confidence: 99%
“…Pointing in great apes represents a flexible, intentional behaviour, since the use of this gesture is adjusted to the attentional state of the human and it occurs in combination with other signals such as facial expressions and vocalizations [19,57,62,63]. Pointing is also frequently used by language-trained apes [60,64,65], where it often resembles the form of the pointing gesture of Western cultures with the arm and index finger extended [66].…”
Section: Gesture Origins (Out Of Actions) (A) Defining a Gesturementioning
confidence: 99%